Penggunaan Istilah Asing (Gairaigo) Review Makeup dalam Kanal Youtube Nanako [Neoki 1-byō]: Kajian Morfologi - Prastika, Tiara Maulina; Kadir, Puspa Mirani; Wagiati, Wagiati (Vocational College of Diponegoro University, 2024)
Language change is a significant impact of the evolution of the times and technological advances, facilitating global cultural communication and interaction. One example of this phenomenon is gairaigo in Japanese, which is an absorbent word from a foreign language and is very commonly used in everyday communication, especially in digital media like YouTube content. Gairaigo plays an important role in modern Japanese, especially in areas influenced by global trends such as makeup. This research aims to study the process of forming the use of gairaigo in reviewing makeup on the YouTube channel Nanako in the study of morphology. Data taken from YouTube with the title